Canada : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
The Canadian monetary and fiscal policies have remained accommodative, reflecting in large measure the effective response to the crisis. Canada is expected to set the appropriate policy mix in the future, at a time of high uncertainty and significant external headwinds. Given the advanced stage of the recovery, a still-large budget deficit, and the need to address long-term fiscal challenges, fiscal policy has moved toward a tightening stance. Resilient household credit has helped sustain private consumption and the construction sector during the crisis.